STUDY OF GENETIC VARIABILITY AND RESPONSE TO SELECTION IN SEGREGATING GENERATIONS OF RICE ( TIONS OF RICE (Oryza sativa sativa L.) CROSS - A. K. CHOUDHARY, (The Bioscan, 2018)
For the trait PPP, exhibited moderate GCV in Istdate of TS, 2nd date of DS and TS. Moderate to high variability were observed in respect to PCV and GCV for GYP plant (g), GYP plot (g) in both the methods of sowing as well as two date of sowing in F3 generation. High h2 coupled with low genetic advance as per cent of mean had recorded for traits DFF in MTL as well as RPS group, which indicated the involvement of non-additive gene action. For trait GPP recorded high h2 coupled with high GA as per cent of mean in Ist and 2nd date of DS as well as TP respectively under HY group whereas high GA along with moderate h2 was obtained in both date of sowing under same selection method indicating the preponderance of additive gene action. Average selection response for all the studied traits had exhibited maximum in LY followed by HY and RPS selection method. In early generation of selection based on the LY criteria as well as high realized h2 would be most effective.